UJI KESESUAIAN STANDAR NILAI HVL FILTER ALUMINIUM PADA PESAWAT SINAR-X MAMMOGRAFI: STUDI KASUS DI RUANG INSTALASI RADIOLOGI RS. SILOAM MAKASSAR - Mutmainna, Azri; Astuty, Sri Dewi; Dewang, Syamsir; Mulyadin, Mulyadin (BERKALA FISIKA, 2020)
The quality control of X-ray radiation in a radiology device plays an important role in determining the clinical use feasibility. The HVL value test of a filter is very important because it determines the effective of X-ray energy. HVL values indicate the thickness of the absorbent material to absorb X-ray intensity up to half of its original intensity. This research is devoted to testing the feasibility of Mammography equipment in the radiology installation room of Siloam Makassar hospital by comparing two methods of determinations the HVL value in the variation of voltage 23, 25, 27, 29, 31 and 33 kVp. The HVL value that determined from direct methods without filters is used as a base value that to be compared with the HVL value which determined by indirect methods through calculations after the addition of aluminum filter thicks to gradually. HVL values by indirect measurements ranged from 0.268−0.401 mmAl, while by direct measurements between 0.291−0.338 mmAl with a deviation between 1.39−7.90%. The results obtained indicate that the HVL value for all X-ray tube voltage variations from the two methods in use still on ranges the tolerance standard so that it can be reported that the X-ray mammography at the Siloam hospital was declared feasible.